Clinical and Economic Impact of Duplicated Radiographic Studies in Trauma Patients Transferred to a Regional Trauma Center. Issue 7 (July 2015) - Hill, Austin D.; Catapano, Joshua S.; Surina, Jeffrey B.; Lu, Minggen; Althausen, Peter L.
Abstract : Objectives: Many trauma patients are evaluated at community hospitals and rural emergency departments before transfer to regional trauma centers. Radiographic studies are often duplicated, leading to significant additional costs to the healthcare system. Our purpose is to identify the reasons for duplicate studies, the costs associated with this practice, and potential clinical effects to patients. Methods: The institutional trauma database was queried to identify patients with orthopaedic injuries transferred to our regional trauma center. Patient demographics, mechanism of injury, referring hospital, reason for transfer, payor source, injury severity score, and Glasgow Coma Score (GCS) were recorded. Duplicate imaging studies were identified and confirmed with each outlying hospital radiology department. The radiation exposure was estimated based on average reported values. The cost of duplicated studies was derived from the Medicare fee schedule. Results: In 1 calendar year, a total of 513 patients were accepted in transfer from 36 outlying facilities. Almost half of the patients (47.7%) had at least 1 radiographic study repeated. There was a significant association between repeated study and age ( P < 0.0001), Injury Severity Score ( P < 0.0001), and GCS ( P < 0.0001). No association was identified for size of transferring institution, injury mechanism, or payor status. Reasons listed for duplication included inadequate data transfer, poor quality, inadequate study, and physician preference. The additional cost to the healthcare system is estimated to be 94, 000. Conclusions: The duplication of imaging studies at regional trauma centers is a common problem that represents a significant opportunity for cost savings and reduction of patient exposure to radiation by implementing imaging protocols at outlying facilities and improving the transfer of imaging data through information technology solutions. Level of Evidence: Economic Level IV. See Instructions for Authors for a complete description of levels of evidence.